PENGARUH BIAYA PRODUKSI DAN PENJUALAN BARANG DAGANG TERHADAP LABA (Studi Kasus Home Industri Tahu Sumedang Sari Bumi) - Reva, Reva Tri Siti (COMPETITIVE, 2023)
Manufacturing companies are companies engaged in the manufacture of goods or products from raw materials that are processed to produce finished products that are ready to be sold to consumers. This study aims to analyze production costs, sales of merchandise on profits during the covid-19 pandemic at a home industry manufacturing company, Sumedang Sari Bumi. The method used is quantitative method, the data source is secondary data in the form of financial statements. The analysis used is a classic assumption test, and a correlation test to find the relationship between variables using financial statement data in 2015-2020. The objects contained in the research are production costs, sales and profits. The results of the study that the increase in production costs with raw materials and sales of merchandise affect the level of profit. In general, every company has a goal, namely to earn profits for the survival of the company. The results obtained by the tests conducted using SPSS show that the variable production costs have a significant effect on profits and sales of merchandise have a significant effect on profits. So it can be concluded that the costs of production and sales of merchandise have a significant effect on profits.